The Mediterranean Sea overturning circulation: A hindcast simulation (1958–2015) with an eddy-resolving (1/36°) model - Mavropoulou, Apostolia-Maria; Vervatis, Vassilios; Sofianos, Sarantis (2022)
The interannual variability of the Mediterranean overturning circulation is investigated using a high-resolution (1/36°) ocean model. As the overturning circulation regulates the replenishment and ventilation of the deep layers, we study the spatiotemporal scales of the maximum value of the overturning streamfunction over three main sub-basins of dense water formation (Aegean Sea, Adriatic, and the northwestern Mediterranean). The variability of the zonal overturning is also discussed. The spectrum analysis shows that the overturning variability has its largest signal on annual timescales in all sub-basins, explained by perpetual winter formation. On shorter frequencies (decadal) there are marked differences observed, due to regional processes of the overturning cells, led by buoyancy flux long-term variability in each sub-basin. The decomposition of the total overturning circulation into barotropic, geostrophic shear, and Ekman components revealed weakening and strengthening for the Aegean and Adriatic Sea total overturning, respectively, with opposite trends for the barotropic and geostrophic shear components. The simultaneous contribution of the Ekman and geostrophic component to the total overturning differentiates the variability of zonal overturning circulation from the local meridional overturning circulation of the three sub-basins. The cross spectra between the maximum overturning value and the buoyancy fluxes also revealed that the system keeps the “memory” of this forcing and shows annual variability.
Keywords: Deep convection; Interannual variability; Mediterranean Sea; Nemo; Overturning circulation; Regional model